Postfire Burnt-Wood Management Affects Plant Damage by Ungulate Herbivores - Jorge Castro (International Journal of Forestry Research)
I analyze the effect of post-fire burnt wood management on herbivore attack on a woody plant species (Ulex parviflorus). Two experimental plots of ca. 20 hectares were established at two elevations in a burnt area in a Mediterranean mountain (Sierra Nevada, Spain). Three replicates of three treatments differing in post-fire burnt wood management were established per plot: “no intervention” (NI, all trees remained standing), “partial cut plus lopping” (PCL, felling the trees, cutting the main branches, and leaving all the biomass in situ), and “salvage logging” (SL; removal of logs and elimination of woody debris). Risk of herbivory and damage intensity were monitored for two years. The pattern of attack by ungulate herbivores varied among treatments and years. In any case, there was an overall reduction in the risk of herbivory in the PCL treatment, presumably because the highest habitat complexity in this treatment hampered ungulate movement and foraging. As a result, the burnt logs and branches spread over the ground acted as a physical barrier that protected seedlings from herbivores. This protection may be used for the regeneration of shrubs and trees, and it is of interest for the regeneration of burnt sites either naturally or by reforestation.